Penggunaan Media Sosial Oleh Peserta Pemilu Pada Masa Tenang: (Pelanggaran Pemilu Atau Kebebasan Berekspresi) - Suling, Derfy (STIH Zainul Hasan Kraksaan Kraksaan, 2024)
The use of social media as a campaign method for election participants is very effective in building broad connectivity and is very efficient in terms of time used when compared to other campaign methods. This shows that campaigns carried out on social media make it very easy for politicians and political parties to carry out campaigns anytime and anywhere so that in other words, campaigns through social media are not limited in space and time It is possible for election participants to use social media during the quiet period in a capacity not as election participants to convey their thoughts and ideas. However, as an election participant, this can be indicated as a form of campaign action. The question of whether this should be considered a form of election violation or a form of freedom of expression is the goal to be answered through this research. The use of social media as a means of campaigning outside the schedule needs to be seen from several different perspectives where the action is a form of election violation, but can also be seen as a form of freedom of expression.